Observations on the Biodegration by Solid State Fermentation of the Giant Swamp Taro (Cyrtosperma merkusii) Biomass by two endolichenic fungi isolates - Helena, Maria; Lawalata, Helen Joan; Rahardiyan, Dino; Rawung, Livana Dethris; Moko, Emma Mauren (Makara Journal of Science, 2024)
Giant swamp taro (GST/Cyrtosperma merkusii), a local North Sulawesi coastal plant, is underutilized but has high po-tential for cultivation as a paludiculture plant on rewetted peatland restorations. GST has high starch content and is currently being explored for potential use. This study explored the potential of using the biomass pulp yielded as resi-dues of the starch extraction process. Endolichenic fungi (Trichoderma reesei and Aspergillus aculeatus) isolated from local lichens, were inoculated on the GST biomass in a solid state fermentation (SSF). Findings of this study indicate that both isolates were effective in degrading the lignocellulosic biomass of GST over an incubation period of 28 days, focusing on cellulose as the targeted polysaccharide. Although T. reesei requires a more adjusted carbon source than A. aculeatus to effectively process the biomass, the effectiveness of the bioprocess after adjustment matched that of A. aculeatus. When hemicellulose is targeted, other strategies must be used to prevent destruction of hemicellulose during the process. This phenomenon should be explored in further studies. These findings indicate the potential of industrial-izing cellulose-based products from GST using local North Sulawesi fungal species abundantly occurring in local eco-systems.